The Democratization of Processes and the Use of Remotely Guided Acquisition Tools for Survey 2.0 (diségno, 2019)
The technology that ‘amplifies’ the real world as well as the technological means of data capturing, are continuing to have a development difficult to control or predict. Projects of a certain interest are born, develop and die sometimes without producing significant results nevertheless becoming phases of a fluid and dynamic process, on which new software applications and hardware systema are built. At the same time, the role of the academy seems to be often overtaken by what is developed by the citizen science. Researchers no longer seem to exclusively explore the ‘discovery’ domain, but rather work at the setup of scientifically reliable protocols for technologies often used by different communities of citizens in a way that does not conform to the specifications for which they were originally designed. This paper focuses on these issues taking as its starting point two experiments with high innovative content that cover various stages of the process defined by the term Survey. They pertain on the one hand to a hw/sw system of data capturing, processing and communication developed for mobile devices (Tango Project) and on the other to a mixed ROV/UAV multisensor platform equipped with a LIDAR system and digital camera for data acquisition in inaccessible places (Heritagebot Project).
Keywords: Google Tango; Heritagebot; Augmented Reality; UAV; Survey